Seed Germination of Pericopsis mooniana Thw. Based on Color and Scarification Techniques - NFN Suhartati; Didin Alfaizin (Jurnal Perbenihan Tanaman Hutan, 2017)
Pericopsis mooniana Thw has a hard seed coat, making it difficult to germinate. This type of seed needs of seed selection and scarification to speed up the germination process, in order to produce a high germination and good seedling. The study aims to increase the value of germination of P. mooniana seed through seed selection based on seed color and scarification techniques. Experimental design used was completely randomized design (CRD) with two factors and three replications. The first factor is seed color (W0 = no selected seeds, W1 = yellowish seeds and W2 = brownish seeds). The second factor is scarification seeds (S0 = without soaked, S1 = soaked in cold water for 24 hours, S2 = soaked in hot water (800C) for 24 hours and S3 = soaked in sulphuric acid/H2SO4 (0.1 M) for 20 minutes. Parameters observed were first time of germination, speed of germination and germination percentage. This study was conducted at the greenhouse, Forestry Research Institute of Makassar in July - August 2015. The result of study showed that yellowish seeds and brownish seed can shortened the time of first germination and increased the germination speed by using scarification technique of seed soaking in hot water to increase germination rate up to 76%.